Protective effects of hesperetin on the quality of sperm, apoptosis, lipid peroxidation, and oxidative stress during the process of cryopreservation: An experimental study - Jamal Valipour; Sina Mojaverrostami; Beheshteh Abouhamzeh; Masoumeh Abdollahi (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Hesperetin is a bioflavonoid compound, largely used in Chinese traditional medicine and found plenty in citrus fruits. Hesperetin has beneficial effects against different diseases. The sperm cryopreservation process is a common method that is used in infertility laboratories. It has been reported that during the cryopreservation process, the quality of sperm is significantly reduced. Objective: To investigate the effect of hesperetin on the quality of human spermatozoa during the cryopreservation process. Materials and Methods: In this experimental study, 22 sperm sample of normozoospermia men who reffered to the infertility department of the Shariati Hospital (Tehran, Iran) Between October and November 2019 were collect and divided in to three groups as: 1) fresh, 2) control (frozen-thawed group without treatment), and 3) treatment group as frozen-thawed samples supplemented with 20 µM hesperetin. Motility, Viability, morphology, Apoptotic-like changes, intracellular H 2 O 2 , intracellular O2 - , and lipid peroxidation (LPO) was measured. Results: Hesperetin treatment during the cryopreservation process of human sperm significantly improved the viability, motility, and morphology rates of the spermatozoa after frozen-thawed process in control group (p < 0.01). In addition, it significantly reduced the reactive oxygen species (ROS) level, LPO level and increased the percentage of viable sperm cells with intact plasma membrane (p < 0.01) after frozen-thawed process. Conclusion: Hesperetin can improve the quality of human sperm and also protect human sperm against reactive oxygen species, LPO, and apoptosis during the cryopreservation-thawing process.